Aboriginal Cultural Narratives and Ecology as Co-Teachers: Understanding Climate Change in the Sensory Classroom on Country - Judith Wilks; Angela Turner; Mark Werner (Australian Journal of Environmental Education)
This paper describes how four rural schools on the mid-north coast of NSW pushed back against the current indoor classroom education model, instead prioritising the importance of ecologising learning beyond the school gate. While there has been considerable attention paid to Aboriginal and/or Torres Strait Islander practices associated with food systems and geographical domains in Australian school curricula, less attention has been paid to the natural Lore of the land and the underlying knowledge and practices shaping and maintaining sustainable land management. Here the authors recount the crucial role of the Gumbaynggirr people’s historical and contemporary cultural knowledge systems that acted as a cornerstone for school students to build their learning about Climate Change authentically with/within nature. Aboriginal knowledge systems derive from a deep relationship between plants and animals, entwined with spiritual practices. However, despite the potential significance of their contributions, Aboriginal and/or Torres Strait Islander people have not been adequately represented in the national discussions about Climate Change (HEAL Network & CRE-STRIDE (2021). Discussion Paper, Lowitja Institute, Melbourne, doi:10.48455/bthg-aj15.). This research found that when representatives from the local Aboriginal community lead teachers in Climate Change education, overwhelmingly student learning is enriched when it occurs in settings enabling a deep relationality with nature and Culture.